The Ontological Miseducation and Ontological Reeducation of African Americans: Race, Resistance and Transformation - Corpening, Brian (My University, 2017)
Carter G. Woodson’s insight that “If you can control a man's thinking you do not have to worry about his action” inspired this dissertation, which critically studies theories of miseducation by Woodson (1933), Jane Roland Martin (2002, 2011), Marcus Garvey (Martin 1976/1986, Brotz, 1999), John Dewey (1916, 1938), Patricia Hill Collins (2009), Franz Fanon (1952/1967, 1959/1965, 1963/2004), Anna Julia Cooper (1892/1989), Paulo Freire (1970/2011, 1974), Noam Chomsky (2000) and William Deresiewicz (2014). This interdisciplinary study re-interprets Ralph Ellison’s life (1919-1994) and his novel Invisible Man (1952/1955) to frame a theory of ontological miseducation (OM), a debilitating hidden curriculum defined by obstacles of indoctrination and control, invisibility, passivity, inability to self-define, zero-sum fallacy, embrace of isms, inflated self-worth, and lack of awareness. Ellison’s work captures the racial relationships that are central to both those “obstructions” of OM and these “beneficials” of ontological reeducation (OR): vision, freedom of thought, affirmation, self-definition, community, humanity, humility and empathy, awareness. This dissertation asks how different individuals and populations, specifically African Americans, have overcome OM’s debilitating impact. How might OM’s targets come to experience the liberating effects of the “beneficials” associated with OR? This inquiry concerning different aspects of OM therefore also analyzes historical cases where African Americans have successfully challenged their own OM and in the process, actually have claimed their OR. This dissertation concludes by offering strategies to engage contemporary populations in solutions that involve critical consciousness and critical resistance that are both necessary to facilitate their transition from OM to OR.
Keywords: African Americans; Miseducation; Ontological